Pengaruh Gugus Hidroksi pada Sintesis Senyawa 4,4’-Dihidroksibenzalaseton dan Aktivitasnya sebagai Antioksidan - Jessica, Maria Anabella; Budiati, Tutuk; Caroline (Faculty of Pharmacy, Widya Mandala Surabaya Catholic University, Indonesia, 2025)
Dibenzalacetone and their derivatives, , 4,4’ dihydroxydibenzalacetone are curcumin analogs that have antioxidant activity. The effect of hydroxyl group on the synthesis reaction is proven by comparing the synthesis results yield of dibenzalacetone with 4,4’-dihydroxydibenzalacetone. Both compounds are synthesized through the Claisen-Schmidt condensation reaction using sodium hydroxide as the catalyst. The synthesis results were tested for purity by melting point tests and thin layer chromatography, and structure identification tests were carried out using infrared spectrophotometry. The results of the study showed that the percentage yield of dibenzalacetone was greater than 4,4’-dihydroxydibenzalacetone, which was 67.29% and 24.51%, respectively. The presence of hydroxyl groups can increase the density of the benzene ring and facilitate the reaction of the carbonyl group of 4-hydroxybenzaldehyde, including the Cannizaro reaction. The Cannizaro reaction can occur in aldehyde compounds without alpha hydrogen, such as benzaldehyde, where some of the aldehyde will undergo oxidation and some will undergo reduction. As a result, the amount of aldehyde that reacts with acetone decreases so that the yield obtained is lessthan dibenzalacetone. Antioxidant testing was carried out using the DPPH method and expressed as an IC50 value, then compared with curcumin and vitamin C. Although it does not show greater antioxidant activity than curcumin or vitamin C, the presence of hydroxyl groups in 4,4' dihydroxydibenzalacetone can increase antioxidant activity compared to dibenzalacetone which does not have a hydroxyl group. This is proven by the IC50 value of the compound 4,4'-dihydroxydibenzalacetone which is lower than dibenzalacetone, which is 3.9588 mM and 66.5503 mM, respectively.